Xanthoderma: an unusual presentation of hypothyroidism. Issue 9 (September 1994) - al-Jubouri, M A; Coombes, E J; Young, R M; McLaughlin, N P
Abstract : A young woman presented with progressive yellowing of her skin over a period of six months. Liver function tests were requested by her general practitioner and the results prompted the Chemical Pathology Department to instigate further tests to reach the final diagnosis. Hypercarotenaemia had caused her yellow skin, and various other biochemical abnormalities pointed towards primary hypothyroidism as an underlying cause. Thyroxine replacement treatment successfully corrected all the biochemical abnormalities including hypercarotenaemia. As far as is known, yellow skin as a sole presenting feature of hypothyroidism is extremely rare.